Pemilihan Tempat Bertelur Nyamuk Aedes aegypti pada Air Limbah Rumah Tangga di Laboratorium - Sudarmaja, I Made; Juwono Mardihusodo, SugengO (Jurnal Veteriner, 2009)
A laboratory experimental study was conducted to observe the types of household waste water as preferential sites for Aedes aegypti to lay their eggs. In this study, three types of waste water were used i.e. soap contaminated water, detergent contaminated water and tap water respectively. The results of the study showed that soap contaminated water (0,5 gram/liter) and tap water were preferential sites for Aedes aegypti to lay their eggs, while detergent contaminated water was not. The number of mosquito eggs found in soap contaminated water was not significantly different with those found in tap water but both of them were significantly higher than those found in detergent contaminated water.
Keywords: Aedes aegypti, eggs, soap, detergent